Rancang Bangun Alat Penampung Buku Berbasis Arduino pada Sistem Pengembalian Buku Layanan Mandiri - Emil Naf’an (Rektorat Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to design and create a book container in a self-service book return system at the Andalusia Library & Knowledge Center UPI YPTK Padang. Currently, the self-service book return system is carried out through a book drop machine. This book container is designed to complement the book drop machine. The returned book is inserted into the slanted gap so that it can slide into the book container. When the book container is empty, the base is at the upper limit position. If a book is entered, the base will automatically drop according to the thickness of the book. And so on, until it is full and the buzzer is active. Thus, it is hoped that book damage can be prevented due to the book falling too far down. The system is designed using ultrasonic sensors to detect upper and lower limits, a Direct Current (DC) motor to move the base down according to the thickness of the book. After testing, the book container works well and is able to withstand loads of up to 22 kg with the number of books between 30 and 50 depending on the size of the book. The DC motor is able to move the book container when the load is maximum. The sensor can detect the thickness of the book, the upper and lower limits and the buzzer can activate when the book is full. Thus, this tool can be used to support the book drop in the self-service book return system.